Biocide treatment for mosquito control increases CH4 emissions in floodplain pond mesocosms - Ganglo, Caroline; Manfrin, Alessandro; Mendoza-Lera, Clara; Lorke, Andreas (Frontiers in Water, 2022)
Shallow lentic freshwater aquatic systems are globally important emitters of methane (CH4), a highly potent greenhouse gas. Previous laboratory studies indicated that bioturbation by chironomids can reduce CH4 production and increase CH4 oxidation by enhancing oxygen transport into sediment. Thus, reduction in chironomid density by application of biocides for mosquito control, such as Bacillus thuringinesis var. israelensis (Bti), have the potential to affect CH4 emissions. We evaluated the effect of a 41% reduction in chironomid larvae abundance due to Bti applications on CH4 dynamics in the aquatic and aquatic-terrestrial transition zones of 12 floodplain pond mesocosms (FPMs) (half treated, half control). We evaluated short-term (2 months) and seasonal effects by measuring CH4 emissions, dissolved concentrations, and oxidation rates in spring, summer, autumn, and winter. On average, CH4 emissions from the aquatic-terrestrial transition zone of the treated FPMs were 137 % higher than those of the control FPMs. The lack of differences in mean oxidation rates between the treated and control mesocosms suggests that a reduction in bioturbation and the associated decreased oxygen transport into the sediment promoted CH4 production in the treated FPMs. Our findings point to potential effects of Bti on CH4 biogeochemistry through alterations of the chironomid abundance, and highlight the underestimated role of invertebrates in biogeochemical cycling in these ecosystems.